Antenatal course of referred monochorionic diamniotic twins complicated by selective intrauterine growth restriction (SIUGR) type III. (2nd December 2021) - Chon, Andrew H.; Ma, Stephen Y.; Korst, Lisa M.; Chmait, Hikmat R.; Purnell, Margaret E.; Chmait, Ramen H.
Abstract: Objective: To describe the antenatal course of selective intrauterine growth restriction (SIUGR) type III patients. Study design: Retrospective study of monochorionic diamniotic twins with SIUGR type III. Patients were divided into those who did and did not progress to SIUGR type II or twin–twin transfusion syndrome (TTTS) (Groups A and B, respectively). Patient characteristics and perinatal survival were compared by Group, and continuous data are reported as median (range). Results: Forty-eight patients were studied; Group A [26 (54.2%)] and Group B [22 (45.8%)]. The difference in 30-day survivorship for the appropriate for gestational age twin (88.5 vs. 100%, p = .2394) and for the SIUGR twin (73.1 vs. 95.5%, p = .0551) was not statistically significant. However, dual survivorship was lower in Group A compared to Group B (69.2 vs. 95.4%, p = .0276). Conclusions: Approximately half of the SIUGR type III patients had antenatal progression. Lack of antenatal progression was associated with 95% dual survivorship. Rationale: The antenatal course of monochorionic diamniotic twins complicated by SIUGR type III is not well-understood and antenatal management remains a clinical dilemma. We provide pregnancy outcomes in a referred group of SIUGR type III patients, including the rate of progression to SIUGR type II and TTTS.